(untitled) (Scientific journal of the Fergana State University, 2024)
The article highlights the issues of the formation of a professional worldview as modern trends in preparing students for professional activity in modern educational conditions, axiological competence related to the worldview of future specialists. While the improvement of mechanisms, technologies and methods of preparing requirements for professional activity is considered as an urgent problem of today, one of the priorities of the pedagogical industry is the professional training of future specialists based on modern approaches. It is also established that the issue of professional worldview has been studied at various times by Eastern scientists and scientists, Western research scientists, educators, psychologists, philosophers and its interpretation in accordance with time in the educational process. With the help of pedagogical diagnostics, knowledge and experience in the field of development and pedagogical correction of students, counseling and training of teachers and parents, professional orientation, professional and personal self-development and the creation of conditions ensuring the unity of these processes are studied. Thus, the article presents the author’s views on this issue on the basis of various approaches, defines criteria and indicators of the professional worldview of students, as well as provides directions, analysis and conclusions on the content of vocational training that students of educational institutions should master.